Advances in traditional Chinese medicine for the treatment of chronic obstructive pulmonary disease. (10th May 2023) - Cao, Xia; Wang, Yi; Chen, Ying; Zhao, Mantong; Liang, Lanyuan; Yang, Mengru; Li, Jianhua; Peng, Mingming; Li, Wei; Yue, Yiming; Zhang, Han; Li, Chuanqiu; et al.
Abstract: Ethnopharmacological relevance: Chronic obstructive pulmonary disease (COPD) is the third leading cause of death globally and thus imposes heavy economic burden on patients, their families, and society. Furthermore, COPD seriously affects the quality of life of patients. The concept of "overall regulation" of traditional Chinese medicine (TCM) plays an important role in the prevention and treatment of COPD. Aim of the study: The objective of this review is to summarize the TCM theories, experimental methods, TCM extracts, active TCM ingredients, and TCM formulas for the treatment of COPD and reveal the effects and mechanisms of TCM treatments on COPD. Materials and methods: This article reviewed literature on TCM-based treatments for COPD reported from 2016 to 2021. Relevant scientific studies were obtained from databases that included PubMed, China National Knowledge Infrastructure, Web of Science, Google Scholar, The Plant List, ScienceDirect, and SciFinder. Results: This review summarized TCM-based theory, experimental methods, active ingredients, and potential toxicities, the effects of TCM extracts and formulations, and their mechanisms for the treatment of COPD. Most investigators have used in vivo models of cigarette smoke combined with lipopolysaccharide induction in rats and in vitro models of cigarette smoke extract induction. The active ingredients of TCM used for the treatment of COPD in relevant studies were triterpenoids, flavonoids, phenolics, quinones, glycosides, and alkaloids. TCMs commonly used in the treatment of COPD include antipyretic drugs, tonic medicines, anticough medications, and asthma medications. TCM can treat COPD by suppressing inflammation, reducing oxidative stress, inhibiting apoptosis, and improving airway remodeling. Conclusions: This review enriches the theory of COPD treatments based on TCM, established the clinical significance and development prospects of TCM-based COPD treatments, and provided the necessary theoretical support for the further development of TCM resources for the treatment of COPD. Graphical abstract: Image 1